2010
DOI: 10.1111/j.1467-8624.2009.01416.x
|View full text |Cite
|
Sign up to set email alerts
|

When Do Children Exhibit a “Yes” Bias?

Abstract: This study investigated whether one hundred and thirty-five 3- to 6-year-old children exhibit a yes bias to various yes-no questions and whether their knowledge status affects the production of a yes bias. Three-year-olds exhibited a yes bias to all yes-no questions such as preference-object and knowledge-object questions pertaining to objects, and knowledge-face questions pertaining to facial expressions. Four-year-olds tended to say "yes" only to knowledge-object questions. Five-year-olds did not show any st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
78
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(90 citation statements)
references
References 29 publications
9
78
3
Order By: Relevance
“…1016/j.jecp.2011.04.012 questions pertaining to various entities such as objects, children's preference for objects, and facial expressions) (e.g., Fritzley & Lee, 2003;, 2010b. These studies found that younger preschoolers consistently exhibited a strong yes bias, but older preschoolers either did or did not exhibit any response bias (Fritzley & Lee, 2003;Okanda & Itakura, 2007, 2010bOkanda, Somogyi, & Itakura, 2011). Given these results, researchers suggested that yes-no questions are not suitable for younger preschoolers (Fritzley & Lee, 2003) or both younger and older preschoolers (Okanda & Itakura, 2010b).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…1016/j.jecp.2011.04.012 questions pertaining to various entities such as objects, children's preference for objects, and facial expressions) (e.g., Fritzley & Lee, 2003;, 2010b. These studies found that younger preschoolers consistently exhibited a strong yes bias, but older preschoolers either did or did not exhibit any response bias (Fritzley & Lee, 2003;Okanda & Itakura, 2007, 2010bOkanda, Somogyi, & Itakura, 2011). Given these results, researchers suggested that yes-no questions are not suitable for younger preschoolers (Fritzley & Lee, 2003) or both younger and older preschoolers (Okanda & Itakura, 2010b).…”
Section: Introductionmentioning
confidence: 94%
“…These studies found that younger preschoolers consistently exhibited a strong yes bias, but older preschoolers either did or did not exhibit any response bias (Fritzley & Lee, 2003;Okanda & Itakura, 2007, 2010bOkanda, Somogyi, & Itakura, 2011). Given these results, researchers suggested that yes-no questions are not suitable for younger preschoolers (Fritzley & Lee, 2003) or both younger and older preschoolers (Okanda & Itakura, 2010b). However, it might not be sufficient to simply avoid using yes-no questions in developmental psychology experiments involving preschoolers; we need to understand why children exhibit these response biases so that suitable questions can be used in future studies with children in this age group.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…We therefore do not ask children to justify behaviour they have already performed, instead ask them to justify their intended actions before they perform them. Thirdly, children's verbal responses may show systematic biases such as answer-switching [35] or a 'yes' bias [36]. We control this possibility by comparing children's justifications for the necessary and unnecessary actions, which are otherwise equivalent.…”
Section: Introductionmentioning
confidence: 99%